Formation conditions and evolution of oil and gas source strata of the Laptev sea shelf ore and gas province - V. Yu. Kerimov; Yu. V. Shcherbina; A. A. Ivanov (Известия высших учебных заведений: Геология и разведка)
Introduction. To date, no unified well-established concepts have been developed regarding the oil and gas geological zoning of the Laptev Sea shelf, as well as other seas of the Eastern Arctic. Different groups of researchers define this region either as an independently promising oil and gas region [7, 8], or as a potential oil and gas basin [1].Aim. To construct spatio-temporal digital models of sedimentary basins and hydrocarbon systems for the main horizons of oil and gas source rocks. A detailed analysis of information on oil and gas content, the gas chemical study of sediments, the characteristics of the component composition and thermal regime of the Laptev sea shelf water area raises the question on the conditions for the formation and evolution of oil and gas source strata within the studied promising oil and gas province. The conducted research made it possible to study the regional trends in oil and gas content, the features of the sedimentary cover formation and the development of hydrocarbon systems in the area under study.Materials and methods. The materials of production reports obtained for individual large objects in the water area were the source of initial information. The basin analysis was based on a model developed by Equinor specialists (Somme et al., 2018) [14—17], covering the time period from the Triassic to Paleogene inclusive and taking into account the plate-tectonic reconstructions. The resulting model included four main sedimentary complexes: pre-Aptian, Apt-Upper Cretaceous, Paleogene, and Neogene-Quaternary.Results. The calculation of numerical models was carried out in two versions with different types of kerogen from the oil and gas source strata corresponding to humic and sapropel organic matter. The results obtained indicated that the key factor controlling the development of hydrocarbon systems was the sinking rate of the basins and the thickness of formed overburden complexes, as well as the geothermal field of the Laptev Sea.Conclusion. The analysis of the results obtained allowed the most promising research objects to be identified. The main foci of hydrocarbon generation in the Paleogene and Neogene complexes and the areas of the most probable accumulation were determined. Significant hydrocarbon potential is expected in the Paleogene clinoforms of the Eastern Arctic.